Clonal selection parallels between normal and cancer tissues. Issue 5 (May 2023) - Salavaty, Abbas; Azadian, Esmaeel; Naik, Shalin H.; Currie, Peter D.
Highlights: Clonal selection and drift (i.e., proliferation and dominance of some cell clones and extinction of others, respectively) are critical phenomena during both normal tissue and cancer development. Stem cells are the key players of clonal selection, utilizing mutation as the major cell-intrinsic variation fuel to drive the selection. Different subclasses of stem cells, each of which is responsible for a distinct feature of the selection process, share common features and functional roles between normal and cancer conditions. Interaction of the stem cells with the surrounding microenvironment is one of the major regulators of the selection process. Clonal selection and drift may indirectly impact on each other in a positive feedback loop. Abstract: Clonal selection and drift drive both normal tissue and cancer development. However, the biological mechanisms and environmental conditions underpinning these processes remain to be elucidated. Clonal selection models are centered in Darwinian evolutionary theory, where some clones with the fittest features are selected and populate the tissue or tumor. We suggest that different subclasses of stem cells, each of which is responsible for a distinct feature of the selection process, share common features between normal and cancer conditions. While active stem cells populate the tissue, dormant cells account for tissue replenishment/regeneration in both normal and cancerous tissues. We also discuss potential mechanisms that drive clonal drift, their interactions with clonal selection, and their similarities during normal and cancer tissue development.